Socioeconomic factors associated with readmission following pediatric tonsillectomy. (December 2021) - Lloyd, Ashley M.; Behzadpour, Hengameh K.; Schonman, Ian; Rana, Md Sohel; Espinel, Alexandra G.
Abstract: Objectives: We aim to analyze factors associated with readmission after tonsillectomy to understand socioeconomic factors associated with readmission. Methods: Single institution retrospective study of pediatric patients undergoing tonsillectomy over an 8 year study period, comparing patients who required readmission for bleeding concerns or pain/dehydration to those who did not require readmission. Results: Of the 14, 152 tonsillectomy patients, 508 (3.6%) were readmitted with 423 (83.3%) for bleeding concerns and 85 (16.7%) for pain or dehydration. Overall readmission was more likely in age >6 years (OR: 1.61, 95% CI: 1.34–1.92, P < 0.001), while poverty level below 10% (OR: 0.79, 95% CI: 0.66–0.94, P = 0.008) and parental college education above 25% (OR: 0.79, 95% CI: 0.65–0.96, P = 0.016) were associated with lower incidence of overall readmission. For patients readmitted for bleeding concerns, age >6 years (OR 1.66, 95% CI: 1.37–2.02, P < 0.001) was associated with readmission on multivariate analysis. Within the pain/dehydration group, African American race was associated with increased readmission rates, while poverty level below 10% and parental college education above 25% were associated with decreased readmission rates. Conclusion: Socioeconomic factors and age play a role in readmission rates following pediatric tonsillectomy.